Integration of an Independent Monitor Unit Check for High-Magnetic-Field MR-Guided Radiation Therapy System - Yang, Jie; Zhang, Pengpeng; Tyagi, Neelam; Scripes, Paola Godoy; Subashi, Ergys; Liang, Jiayi; Lovelock, Dale; Mechalakos, James; Li, Anyi; Lim, Seng B. (Frontiers in Oncology, 2022)
Purpose: Commercial independent monitor unit (IMU) check systems for high magnetic field MR-guided RT systems are lacking. We investigated the feasibility of adopting a commercial treatment planning system (TPS) as an IMU check for online adaptive radiotherapy using 1.5 Tesla MR-Linac. Methods: The 7 MV flattening-filter-free (FFF) beam and multi-leaf collimator (MLC) models of a 1.5T Elekta Unity MR-Linac within Monte Carlo-based Monaco TPS was used as the reference to generate a similar FFF beam in Eclipse TPS using the AAA algorithm. The MLC dosimetric leaf gap of the beam in Eclipse was determined by matching the dose distribution of Eclipse generated IMRT plans to Monaco. The plans were automatically adjusted for different SAD (143.5 cm vs. 100 cm) between the two systems. For IMU check, the treatment plans developed in Monaco were transferred to Eclipse to recalculate the dose using AAA. A plug-in within Eclipse was created to perform a 2D gamma analysis of the AAA and Monte Carlo dose distribution on a beam’s eye view parallel plane. Monaco dose distribution was shifted laterally by 2 mm during gamma analysis to account for the impact of magnetic field on electron trajectories. Eclipse doses for posterior beams were corrected for both the Unity couch and the posterior MR coil attenuation. 13 patients, each with 4-5 fractions for a variety of tumor site (pancreas, rectum, and prostate) were tested. Results: A total of 62 online plans, each with approximately 15 beams were evaluated. The average per-beam gamma (3%/3mm) pass rate for plans was 97.9% (range: 95.9% to 98.8%). The average pass rate per beam for all 932 beams used in these plans was 97.9±1.9% with the lowest per-beam gamma pass rate at 88.4%. The time for the process was within 3.2±0.9 minutes Conclusion: Eclipse TPS can provide an efficient way to perform IMU check with clinically acceptable accuracy for online adaptive plans on Unity MR-Linac.